Pengaruh Bantuan Operasional Sekolah Dan Motivasi Orang Tua Terhadap Prestasi Akademik Siswa Madrasah Ibtidaiyah Se Kecamatan Banjarejo Kabupaten Blora Tahun 2015 - Waluyo, Yoyok (2016)
The aim of the research are to describe : 1) influence of school operations subsidy towards students academic achievement at Islamic Elementariy School (MI) at Banjarejo. 2) influence of parents motivation towards students academic achievement at Islamic Elementariy School (MI) at Banjarejo. 3) influence of school operations subsidy and parents motivation towards students academic achievement at Islamic Elementariy School (MI) at Banjarejo. The type of the research is a quantitative research. The data obtained using covered questionnaires with stratified random technique is a way to obtain the data at random and based on the criteria. The questionnaire was completed by 195 respondents (20% of 975 population) of MI at Banjarejo Blora. The data were analyzed using the technique of "Multiple Correlation Analysis". While testing the hypothesis using product moment analysis comparing the count of r with table of r to know the relationship between the use of the school operations subsidy, Parents Motivation to student achievement at MI at Banjarejo. The results of this research show that: 1) There is no significant influence between the use of the School Operations Subsidy towards student academic achievement at MI at Banjarejo Blora. Only 21.5% of students at MI at Banjarejo who feel the impact of maximal utilization of BOS, 24.1% of students feel that the BOS utilization is still low, and 54.4% felt in the medium category. 2) There is no significant influence between the parents motivation towards student academic achievement at MI at Banjarejo Blora. The results showed that only 9.2% of parents who give motivation to the child to the maximum, 33.3% giving motivation in the low category, while 57.4% in the medium category. 3) There is no significant influence between the use of the School Operations Subsidy and the parents motivation toward student academic achievement at MI at Banjarejo Blora. The relationship between the use of the School Operations Subsidy (BOS) and the parents motivation toward student academic achievement are positive, that mean the higher utilization of BOS and motivation by the parents, the higher the academic achievement of students at MI at Banjarejo Blora. It is clear that the School Operations Subsidy (BOS) at MI at Banjarejo not maximum utilized. Similarly, the motivation of the parents have not given to the maximum.